2019
DOI: 10.17821/srels/2019/v56i2/141631
|View full text |Cite
|
Sign up to set email alerts
|

Use of Internet through Mobile Devices: A Survey

Abstract: The purpose of this paper is to examine the use of Internet through mobile devices. This study was conducted using a questionnaire. Findings reveal that most of the respondents admit the importance of the Internet in their day-to-day life. Over three fourths (79%) of them have access to the Internet on their mobiles and majority (84.8%) preferred accessing Internet at home.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Additionally, 79% of people use mobile devices to access the internet, making it simple to connect to social networking sites. 16,17 These data show how commonplace internet use has become, as well as how much more people are relying on mobile devices for online activity. Another study by Dobson et al, found that a substantial number of participants use social media sites for both personal and professional reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, 79% of people use mobile devices to access the internet, making it simple to connect to social networking sites. 16,17 These data show how commonplace internet use has become, as well as how much more people are relying on mobile devices for online activity. Another study by Dobson et al, found that a substantial number of participants use social media sites for both personal and professional reasons.…”
Section: Discussionmentioning
confidence: 99%
“…This may be aggravated when there is the existence of other influences such as anxiety or anguish, which were not part of this analysis. Even the excessive use of technology can cause variations in sleep patterns, as cited (Shimray & Ramaiah, 2019). However, this was not straight established in our study, but it is reflected that it can be further studied in upcoming work.…”
Section: Discussionmentioning
confidence: 64%
“…A final interrogation linked to the prolonged use of technological devices for leisure activities was added to the questionnaire. Since (Shimray & Ramaiah, 2019) points out that the world average is about seven hours of daily use, it was recognized four hours (excluding academic activities) is a referential value that can specify excessive use. Contrary to what was expected, there was no substantial connection was found among the devices and the instruments used.…”
Section: Resultsmentioning
confidence: 99%
“…They also allow strengthening the communication with core ties and promote day-to-day coordination and safety (Marler, 2018). Therefore, disadvantaged populations use smartphones to get online for the first time and mobile-only use represents an access opportunity for them (Ensley, 2005; Pearce and Rice, 2013; Shimray and Ramaiah, 2019). However, there is a consensus that the digital inclusion is a multidimensional process to achieve a meaningful and effective use of the potentialities of the web (e.g.…”
Section: Mode Of Accessmentioning
confidence: 99%